The cross-species mycobacterial growth inhibition assay (MGIA) project 2010-2014 - Brennan, M; Tanner, R; Morris, S; Scriba, T; Achkar, J; Zelmer, A; Hokey, D; Izzo, A; Sharpe, S; Williams, A; Penn-Nicholson, A; Erasmus, M; et al. (American Society for Microbiology, 2017)
The development of a functional biomarker assay in the tuberculosis (TB) field would be widely recognized as a major advance in efforts to efficiently develop and test novel TB vaccine candidates. We present preliminary studies using mycobacterial growth inhibition assays (MGIAs) to detect a BCG vaccine response across species, and extend this work to determine if a standardized MGIA can be applied in characterizing new generation TB vaccines. The comparative MGIA studies reviewed here aimed to evaluate robustness, reproducibility, and ability to reflect in vivo responses. In doing so, they have laid the foundation for the development of an MGIA that can be standardized and potentially qualified. The major challenge ahead lies in better understanding the relationship between in vivo protection, in vitro growth inhibition and the immune mechanisms involved. The final outcome would be an MGIA that can be used in confidence in TB vaccine trials. We summarize data arising from this project, present a strategy to meet the goals of developing a functional assay for TB vaccine testing, and describe some of the challenges encountered in performing and transferring such assays.